„Społeczeństwo jako ciało jest pęknięte”. Zabiegi stylizacyjne w dialogach Małgorzaty Szumowskiej i Michała Englerta na przykładzie filmów Body/Ciało i Twarz - Miławska-Ratajczak , Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The aim of this article is to present an overview of the stylistic measures identifiable in the dialogues of two films whose screenplays were written by Małgorzata Szumowska and Michał Englert – Body (2015) and Mug (2017). The analysis of linguistic and stylistic means has been organised into three categories that can be used to describe the work of this script-writing duo (in line with Adam Kruk’s critical proposition): deliberate schematicity, social hearing (as a metaphor for social sensitivity) and mockery. In the linguistic layer of these films, schematicity comes to the fore through the accumulation of homogeneous linguistic means (especially from the emotional register of colloquial Polish) and contrasting juxtapositions of various social variants of the language. The social hearing of Szumowska and Englert is revealed especially through the presence of linguistic templates, and mockery – in the linguistic joke and in the openly mocking statements of some of the characters. The analysis shows that the dialogues are another testimony to the stylish separateness of Szumowska and Englert and one of the ways to portray Poland as full of internal divisions.